The Relationship Between Internet Addiction and Anxiety Levels in Adolescents at SMA Islam Sabilal Muhtadin Banjarmasin - Rahmasari, Najwa; Syafwani, M; Hamsanie, Mohamad; Anwari, Muhammad (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Excessive internet use among adolescents may affect mental health, including increasing anxiety. This study aimed to determine the relationship between internet addiction and anxiety levels among adolescents at SMA Islam Sabilal Muhtadin Banjarmasin. This study employed a quantitative correlational design with total sampling, involving all Grade X and XI students who met the criteria, totaling 50 respondents. Research instruments were the Internet Addiction Test (IAT) and the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using Pearson correlation test. The results showed levels of internet addiction: none 6 (12.0%), mild 21 (42.0%), moderate 23 (46.0%); and anxiety levels: none 8 (16.0%), mild 24 (48.0%), moderate 14 (28.0%), severe 4 (8.0%). Pearson correlation yielded r = 0.665 with p < 0.001, indicating a positive and significant relationship between internet addiction and anxiety levels. Higher internet addiction scores were associated with higher levels of anxiety. It is recommended that schools and parents monitor internet use and implement mental health education programs for adolescents.